Interactions between infernan and calcium: From the molecular level to the mechanical properties of microgels. (15th September 2022) - Zykwinska, Agata; Makshakova, Olga; Gélébart, Perrine; Sinquin, Corinne; Stephant, Nicolas; Colliec-Jouault, Sylvia; Perez, Serge; Cuenot, Stéphane
Abstract: With the increasing need for hydrogels with tunable properties for specific biomedical applications, a complete understanding of the structure-function relationship of polymers used for hydrogel development remains crucial for their optimal use. In the present study, by combining experimental and theoretical approaches, the structure-function relationship of a bacterial exopolysaccharide, infernan, displaying both glycosaminoglycan-mimetic and gelling properties, was investigated at molecular and microscopic levels. Atomic force microscopy (AFM) experiments and molecular dynamics simulations were applied to determine the persistence length of individual infernan chains before studying their association induced by calcium. Infernan-based microgels were then produced using microfluidics and their mechanical properties were characterized by AFM methods. The mechanical properties of EPS/calcium microgels were finely tuned by varying the crosslinking density of their network, either by calcium or EPS concentrations. The obtained set of viscoelastic microgels with different elastic modulus values opens several possibilities for their applications in tissue engineering. Graphical abstract: Unlabelled Image